Development of A Learning Video on The Discovery of Integer Numbers to Improve Mathematical Problem-Solving Abilities and Creative Thinking Abilities of Grade VI Students - Oktaf Winda Wanodya Utama; Tatag Yuli Eko Siswono; Tri Dyah Prastiti (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to develop a discovery-based mathematics learning video on integer material that can improve mathematical problem-solving skills and creative thinking skills of grade VI elementary school students. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were grade VI students at an elementary school in Punggul Gedangan. The instruments used included validation sheets from material experts, design experts, media experts, and mathematics teachers, student response questionnaires, and problem-solving and creative thinking ability tests. The validation results showed that the developed learning video was included in the very valid category. Limited trials showed that the video was effective in improving students' problem-solving and creative thinking abilities. Thus, the developed learning videos are suitable for use as alternative learning media in mathematics learning, especially integer material, and can support students' high-level thinking skills.